Influence of blade leading-edge form on the performance and internal flow pattern of a mixed-flow pump - Huo, Zhenggang; Zha, Xiaoting (Frontiers in Energy Research, 2023)
In this article, a typical mixed-flow pump was adopted as the research object to investigate the influence of the inlet structure within the impeller on the performance and internal flow patterns of the mixedflow pump. Firstly, three different blade inlet structure cases, which are forward bending, straight, and backward bending, were proposed and modeled separately. Secondly, the performance of mixed-flow pumps featuring different cases was carefully compared and analyzed. The results show that the inlet structure of the blades has a small impact on the head of the mixed-flow pump. However, it has a significant impact on the efficiency and shaft power of the pump at the rated flow condition. Among them, the performance of the straight and backward bending cases is significantly better than that of the front bending case. At the same time, the accuracy of the numerical results was verified by the experimental results. Finally, the internal flow and hydraulic loss laws with different inlet structure were deeply studied. It is found that the case of forward bending will cause the media to strike the middle of the inlet edge of the blade first, and then generate secondary flow along the inlet edge. The secondary flow will induce stronger media crowding at the inlet side near the shroud and hub. Due to the large curvature of the shroud and hub at the position of intersection with the inlet side of the blade, media crowding induces flow interference of the media on each span of the impeller channel. This ultimately leads to increased flow losses within the impeller and diffuser, reducing the hydraulic performance of the mixed-flow pump. This finding clarifies the influence mechanism of the inlet side geometry of the inlet blade on the performance and internal flow of the mixed-flow pump, which can provide a theoretical basis for improving the performance of the mixed-flow pump.